Effect of cadmium and lead on the morphology and protein profile of Calligonum comosum seeds - Alotaibi, Modhi O. (Frontiers in Ecology and Evolution, 2024)
Soils contaminated with heavy metals (HMs) pose a risk to human health via the food chain, as many edible plants absorb these metals. In turn, some of these plants could be used as phytoremediators for such soils. Calligonum comosum is an indigenous medicinal shrub that grows naturally in wide swaths of sandy soil in Saudi Arabia and has many advantages that render it a promising candidate for the treatment of HM-contaminated areas. But the impact of HM on this plant remains unknown, especially in the early stages of its development.Objective: This investigation aimed to study the effects of lead (Pb) and cadmium (Cd) on the germination of C. comosum seeds under laboratory conditions, and assess the seeds' response to these metals.The C. comosum seed germination was monitored in Petri dishes containing Pb and Cd at increasing concentrations (25, 50, 75, and 100 µM) for up to 3 weeks. SDS-PAGE was used to examine the protein profile of germinated seeds and the western blot was used to assess the influence of HMs on the activities of the catalase enzyme and the beta subunit of ATP synthase (AtpB).The germination rate and speed of C. comosum seeds were delayed by increasing concentrations of either Pb or Cd, but this effect was dose-dependent. SDS-PAGE analysis results revealed that exposure to both metals led to altered protein profiles as indicated by the resulting band intensities and disappearance of some proteins compared with the untreated controls. Further, the western blot analysis detected greater activity of catalase enzyme as well as AtpB in the Cd-and Pbtreated seeds.C. comosum seeds treated with Cd or Pb enhance protein degradation and denaturation beside oxidative stress, leading to reduced seed viability. These results suggest oxidoreduction proteins 2 This is a provisional file, not the final typeset article and those involved in ATP synthesis are enhanced in C. comosum seeds in response to Cd and Pb stressors, which is a probable mechanism by which seeds may tolerate heavy metal stress.